2012
DOI: 10.1159/000336837
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal Anti-Inflammatory Drugs Alter the Human Mesothelial Pleural Permeability via Ion Cellular Transportation by Inhibiting Prostaglandin Synthesis

Abstract: Background: Nonsteroidal anti-inflammatory drugs (NSAIDs) are used in clinical practice as analgesics or anti-inflammatory drugs. Studies have implicated them in participating in permeability throughout various tissues such as the kidneys and lungs. Objective: The effect of NSAIDs on the pleural permeability and the underlying mechanisms whereby this effect is mediated were investigated. Methods: Parietal pleural specimens were obtained from patients subjected to thoracic surgery and were mounted in Ussing cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
7
0
1
Order By: Relevance
“…Although these studies did not include a mapping of the expression in pleura as shown e.g., on functional level (Kouritas et al, 2008), they might become important for the understanding of pathophysiological regulatory mechanisms of transcellular pleural transport, shown for histamine and prostaglandins, recently (Kouritas et al, 2011, 2012). …”
Section: Transport and Barrier Mechanisms In Pleura Mesotheliummentioning
confidence: 99%
“…Although these studies did not include a mapping of the expression in pleura as shown e.g., on functional level (Kouritas et al, 2008), they might become important for the understanding of pathophysiological regulatory mechanisms of transcellular pleural transport, shown for histamine and prostaglandins, recently (Kouritas et al, 2011, 2012). …”
Section: Transport and Barrier Mechanisms In Pleura Mesotheliummentioning
confidence: 99%
“…Decreases in production of prostaglandins play a critical role in subsequently decreasing the permeability of the pleura, leading to increased pleural fluid and reduction in clearance of pathogens 11, 14, 23 . NSAIDs might also paradoxically increase inflammatory response within the lungs, as indicated by greater white blood cell migration, in particular, neutrophils 13, 14 . It is also possible that the use of NSAIDs can decrease severity of symptoms of respiratory infection, thereby delaying hospitalization and proper treatment 3, 12 …”
Section: Discussionmentioning
confidence: 99%
“…Observational studies have indicated an increased risk of pneumonia complications associated with NSAIDs in this patient population 3–12 . It has also been hypothesized that NSAIDs, like ibuprofen, can induce proinflammatory cascades that may increase inflammatory response within the lungs, as indicated by greater white blood cell migration, particularly neutrophils 13, 14 …”
mentioning
confidence: 98%
“…NSAIDs were shown to hinder pleural permeability ex vivo, by inhibiting prostaglandin synthesis and eventually blocking the epithelial sodium channel ENaC and the Na þ / K þÀ ATPase activity normally operating in the pleura [30]. In vivo experiments also demonstrated that NSAIDs limited the absorption of provoked hydrothoraces, by reducing the acute and late absorption rate and thus the volume of the hydrothorax eventually absorbed [29,31]. Additionally, NSAIDs induced increased white cell migration within the pleural cavity with a higher percentage of neutrophils present, indicating the initiation of an inflammatory response in the remaining hydrothorax [29,31].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo experiments also demonstrated that NSAIDs limited the absorption of provoked hydrothoraces, by reducing the acute and late absorption rate and thus the volume of the hydrothorax eventually absorbed [29,31]. Additionally, NSAIDs induced increased white cell migration within the pleural cavity with a higher percentage of neutrophils present, indicating the initiation of an inflammatory response in the remaining hydrothorax [29,31]. It is highly likely that NSAIDs have a similar effect in parapneumonic effusions; their effects on ENaC and Na þ ÀK þ ATPase decrease the absorption rate of the pleural fluid and pathogen clearance allowing potential pathogens to lead to complicated pleural effusion [32].…”
Section: Discussionmentioning
confidence: 99%